Professional Training of Future Masters of Primary Education to Innovative Activities Through the Prism of a Competence Approach - Oksana Tsiuniak (Vasyl Stefanyk Precarpathian National University, 2020)
The current problems of the advanced system, which were most often used by masters who were studying for innovation, are updated. Theoretical analysis of scientific sources with understanding of the concept of "personal approach" is carried out. Changes of important aspects that are covered by methodological research in the field of work carried out in future Master's workplaces are analyzed. The essence and peculiarities of realization of the competence approach in the system of professional preparation of future masters of elementary education for innovative activity are considered. It is noted that the competence approach is aimed at the results of education not as a sum of learned information, but as the ability of a future specialist to creatively use the acquired knowledge in practice. It is concluded that the implementation of a competent approach in the system of training of future masters of elementary education in innovation ensures the achievement of a high level of quality professional training, the result of which is the competent personality of a future specialist, competitive in the labor market, able to act in an innovative educational environment.